Relation between aortic knob width and subclinical left ventricular dysfunction in hypertensive patients. (18th August 2018) - Gürbak, İsmail; Yıldız, İbrahim; Panç, Cafer
ABSTRACT: Background : The assessment of left ventricular (LV) structure and function is important in the evaluation of hypertensive heart disease, as it provides information on the cardiovascular morbidity and mortality. Aortic knob width (AKW) is a measurement of radiographic structure formed by the foreshortened aortic arch and a portion of the descending aorta. The main aim of this study was to investigate the relation between AKW on the routine chest radiography and subclinical LV dysfunction in hypertensive patients. Patients and Methods : A total of 144 patients with hypertension admitted to the cardiology outpatients clinic were enrolled consecutively. The patients were divided into two groups according to tissue Doppler-derived myocardial performance index (MPI): subclinical LV dysfunction group (abnormal MPI ≥ 0.5, n  = 85) and absence of subclinical LV dysfunction group (normal MPI< 0.5, n  = 59). Results : Patients with subclinical LV dysfunction were older (60 ± 8 vs. 54 ± 8, p  = 0.001). Left ventricular mass index (LVMI) (96 ± 27 vs. 74 ± 24, p  < 0.001) and prevalence of LV hypertrophy (28 vs. 8%, p  = 0.011) were significantly different between two groups. Patients with subclinical LV dysfunction had higher AKW (42 ± 6 vs. 34 ± 5, p  < 0.001) compared with patients without subclinical LV dysfunction. There was a significant correlation between MPI and AKW ( r  = 0.7, p  < 0.001). Multiple logistic regression analysis showed that AKW ( β  = 0.617, p  = 0.001) and posterior wall thickness (PWth) ( β  = 1.189, p  = 0.021) were independently associated with subclinical LV dysfunction. Analysis using the Receiver Operating Characteristic (ROC) curve has demonstrated that aortic knob of 37 mm constitutes the cutoff value for the presence of subclinical LV dysfunction with 85.9% sensitivity and 86.4% specificity (The Area under the Curve ± Standard Error (AUC±SE) = 0.916 ± 0.024, p  < 0.001). Conclusion : AKW may provide important predictive information on subclinical LV dysfunction in patients with hypertension.